Analisa UI/UX Terhadap Perancangan Website Laundry dengan Metode Human Centered Design dan User Experience Questionnaire - Salsabilah, Salsabilah; Wahyuddin, Moh. Iwan; Sari, Ratih Titi Komala (STMIK Budi Darma, 2022)
The development of information technology today has developed very rapidly where in its development can help people from all walks of life in doing anything, one of which is in the laundry service business sector. My laundry is one of the businesses that offer Laundry services that provide kiloan washingservices. In My laundry In doing data collection or recording my laundry data still does manually. In solving the problems that occur in my laundry system the solution is to apply an information technology system that uses a website. In a design of user interface and user experience can be used as basic things in the creation of a website. In conducting analysis and design of user interface and user experience using the Human Centered Design (HCD) approach and user experience questionnaire (UEQ) method is expected to provide conveniencefor users of the website